Final Paleolithic sites in Kuyavia - Płaza, Dominik; Wicha, Joanna; Papiernik, Piotr (Acta Archaeologica Lodziensia, 2018)
Kuyavia is one of the richest regions in archaeological finds especially in stone age archaeology. Unfortunately for a long time there were almost no data about Paleolithic sites. The first insubstantial information came from the Polish Archaeological Research Project from late 70-ties when the first Paleolithic flint were identified. A new perspective appeared around 2010 and the beginning of PhD research about Mesolithic in Kuyavia when all Final Paleolithic sites from archive of Polish Archaeological Research were registered (Płaza 2015). This research showed around 30 sites which could be indirectly linked with Final Paleolithic cultures. During last few years several further Final Paleolithic sites have been identified during field walking studies connected with execution of project “Archaeological sources in the region of Wietrzychowice Culture Park” supported by Ministry of Culture and National Heritage. All the data collected suggests that in the near future much more Final Paleolithic sites ought to be found in Kuyavia.